Formulating Risk Mitigating Strategies: A Case Study on Maritime Cyber Security Regime and Awareness at Penang Port Commission (PPC) (S/O 13756) - Arbak, Salwani; Ali, Nik Nor Suhaida; Ahmad, Mohammad Zaki; Yaakob, Sabariah; Abdul Ghani, Ahmad Bashawir (UUM, 2023)
Today, maritime port industry plays a critical role in the global supply chain, facilitating the transportation approximately 80% of world trade by volume. Notwithstanding the importance of maritime ports in acting as a conduit for a smooth interchange between goods and shipping lines, the worldwide trend of digitalization of port operational framework and ecosystem has gained visible traction over the last twenty years. Whilst digital technology could enhance port efficiency and competitiveness, a new area of vulnerabilities emerged. Port operations and activities are now more than ever exposed to a very real and potentially damaging risk of malicious cyber threats and attack. The recent Incidents of cyber-attack on maritime industry worldwide have been widely reported in both mainstream and social media. Major shipping lines, as well ports and shipping terminals have been falling victim to malicious cyber-attack, resulting substantial financial loss, operational disruption and even reputation damage...